Remembering the Present: Mindfulness in Buddhist Asia - Cassaniti, Julia (Cornell University Press, 2018)
What is mindfulness, and how does it vary as a concept across different cultures? How does mindfulness find expression in practice in the Buddhist cultures of Southeast Asia? What role does mindfulness play in everyday life? J. L. Cassaniti answers